2016
DOI: 10.1097/wnr.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of delta opioid receptor agonist (D-Ala2, D-Leu5) enkephalin on permanent focal cerebral ischemia in rats

Abstract: To investigate the effect of delta opioid receptor agonist (D-Ala, D-Leu) enkephalin (DADLE) on the permanent focal cerebral ischemia in rats. Thirty four male Sprague-Dawley rats were assigned randomly into three groups: sham group (group Sham, n=10), artificial cerebrospinal fluid group (group ACSF, n=12), and DADLE group (group DADLE, n=12). Permanent middle cerebral artery occlusion was performed to induce permanent focal cerebral ischemia in rats. Then, the animals in group DADLE and group ACSF were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…More importantly, a growing body of evidence has shown that the neuroprotective effect of DOR activation is related to MAPK signalling during ischaemia/hypoxia. For example, treatment with the DOR agonist [D-Ala2, D-Leu5]-enkephalin (DADLE) extends the neuronal survival rate during permanent focal cerebral ischaemia in rats (Fu et al 2016). Perfusion with DADLE also provides neuroprotection against oxygen-glucose deprivation (OGD)-induced neuronal injury by affecting the phosphorylation of extracellular signal-regulated kinases (ERKs) and p38 but not c-Jun N-terminal kinase (JNK) (Ke et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a growing body of evidence has shown that the neuroprotective effect of DOR activation is related to MAPK signalling during ischaemia/hypoxia. For example, treatment with the DOR agonist [D-Ala2, D-Leu5]-enkephalin (DADLE) extends the neuronal survival rate during permanent focal cerebral ischaemia in rats (Fu et al 2016). Perfusion with DADLE also provides neuroprotection against oxygen-glucose deprivation (OGD)-induced neuronal injury by affecting the phosphorylation of extracellular signal-regulated kinases (ERKs) and p38 but not c-Jun N-terminal kinase (JNK) (Ke et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Peptide 23 is a selective delta-opioid receptor agonist which displays protective effects towards the preservation of neurologic function and neuronal damage against hypoxic or ischemic induced brain injury. [27] Peptide 23 was functionalized with succinimidyl ester 22 to afford DIBAC-peptide conjugate 24 . The desired 4-[ 18 F]fluorophenyl sydnone 4b (6–10 mCi) was purified and isolated within 62 min from the end of bombardment in 21 ± 3% non-decay-corrected radiochemical yield (RCY) (n=17) with a specific activity of 1.3 Ci μmol −1 .…”
mentioning
confidence: 99%
“…The rats in the sham group underwent the same surgical operations except for the monofilament insertion. Statistically, the total mortality was 21% [ 23 , 25 ].…”
Section: Methodsmentioning
confidence: 99%